MicroRNA expression profile in Lampetra morii upon Vibrio anguillarum infection and miR-4561 characterization targeting lip - Lie Ma (Nature Portfolio, 2021)
Ma et al characterise differentially expressed miRNAs in Lamprey upon bacterial infection. They identify miR-4561 as being decreased after infection and show that it targets the 3′UTR of the mRNA encoding lamprey immune protein (LIP) involved in lamprey innate immunity and regulates survival in lamprey embryos.